Changing Ohio Corrections - Rhine, Edward E. (Victims & offenders, 2021)
Ohio corrections has demonstrated an impressive and growing commitment to reform shaped by the extraordinary reach and collaborative efforts of Ed Latessa. Joining the University of Cincinnati as an assistant professor of criminal justice in 1980, Ed went on to grow the program in size and reputation and helped catalyze key rehabilitative ideas, collaborative networks, and research institutions over the next four decades. Through an “Ohio-centric” lens, this paper seeks to highlight Latessa’s unwavering devotion to helping correctional agencies adopt and implement evidence-based practices and the lasting imprint of his expansive portfolio of work that started in the Buckeye State.